Emergency Installation Staff Satisfaction with the Use of Electronic Medical Records - Nurfadilla, Destiani Irma; Sutha, Diah Wijayanti; Wahyuni, Titin; Rahmawati, Ayu Isnaini (Jurnal Ilmiah Kesehatan, 2025)
Proper implementation of electronic medical records (EMRs) is essential to increase health worker satisfaction, which in turn improves the quality of health services. However, the use of EMR can also cause dissatisfaction, in part due to limitations in sentence format when completing medical assessments in the EMR system. This study aims to explore the relationship between the use of EMR and the satisfaction of health workers in the emergency room of RSMM (Rumah Sakit Mata Masyarakat), East Java. With a quantitative analysis approach, this research used a cross-sectional design with 19 participants selected through a total sampling method. This research focuses on two main variables: officer satisfaction (free) and EMR use (bound). Data was collected through interviews and questionnaires, and statistical analysis was carried out using the Spearman test. Findings showed that 63.2% of respondents were satisfied, with 78.9% expressing confidence in the quality of EMR use. The Spearman test produced a significant p-value of 0.006 (p < 0.05), indicating a significant relationship between the use of RME at RSMM East Java. RSMM East Java is committed to continuing to increase personnel satisfaction by continuously improving the EMR system based on feedback.